Evaluasi Praktik Hukum Dalam Sistem Administrasi Negara Modern - Setianingsih Susilorini, Endang; Sulistyawati, Reni (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This study discusses the evaluation of legal practice in the context of modern state administrative systems. This study aims to analyze the effectiveness and relevance of applied legal practices in carrying out administrative tasks in the modern era. Research methods used include analysis of legal documents, case studies, and reviews of related literature. The findings of this study provide in-depth insight into how law plays a role in regulating and supervising state administrative activities, as well as the implications of such evaluations on the improvement of the overall state administrative system. The results of the analysis also identify the main challenges and innovations needed in dealing with complex dynamics in the modern state administrative environment. In conclusion, the evaluation of legal practice in the modern state administration system is an important step to ensure effective, transparent, and compliant governance with the principles of law and justice in serving the public interest.